Ethnobotanical Study of Plants Used by Traditherapists for the Treatment of Malaria in the City of Butembo, North Kivu, East of the Democratic Republic of Congo - Muhindo Aristote Syamasamba; Musubao Moïse Kapiri; Kambale Eloge Muhesi; Kagheni Eugène Mbayahi; Blaise Mbala Mavinga (CV. Literasi Indonesia, 2022)
Malaria is a serious public health problem in the Democratic Republic of Congo (DRC) in general and in the city of Butembo in particular. To complete the lack of information, the objective of this article is to identify the different plant species used in the traditional treatment of malaria in the city of Butembo. Ethnobotanical investigations were conducted among 91 traditherapists. Semi-structured interviews with the use of a pre-established questionnaire were used for data collection. This study allowed the inventory of 26 plant species belonging to 18 botanical families. The species of the Asteraceae family are the most solicited by the therapists of the city of Butembo (25.27%). This family is followed by the Myrtaceae and Rubiaceae families, each with a total of 12.09%. Then come the Caricaceae, Poaceae, and Fabaceae with respectively 9.89%, 9.89%, and 8.79% of citations. Leaves are the most used organ (70.33%) in the preparation of drugs. The pharmaceutical form of preparation is decoction (81.32%). The antimalarial recipes are administered by oral (100%). The species most solicited by the therapists are Artemisia annua (12.09%), Eucalyptus maideni var globulus (10.99%), Cinchona ledgeriana (10.99%), Cymbopogon citratus (9.89%), Carica papaya (9.89%), Cassia occidentalis (7.69%), and Bidens pilosa (8.79%). In consideration of these results, phytochemical and pharmacological analysis of these plants is essential to help validate their traditional use and to find new plants with antimalarial potential that would play the first role in the development of improved traditional medicines (ITM) with antimalarial activity.